Determination of some natural inhibitors of pepsin, trypsin and chymotrypsin in several invertebrate and fish species along the Romanian coast of the Black Sea - Roșoiu, Natalia; Șerban, Mihai; Panait, Maria (Cercetări Marine - Recherches Marines, 2026)
The paper is presenting preliminary data on some natural inhibitors of pepsin, trypsin and chymotrypsin in the protein extracts from Actinia aeguina. Rapana thomasiana, Scrnalus acanthias, Odontogadus merlangus euxinus and Engraulis encrassicholus ponticus.